2017
DOI: 10.15671/hjbc.2018.207
|View full text |Cite
|
Sign up to set email alerts
|

Can Food Supplement Produced from Apilarnil be an Alternative to Testosterone Replacement Therapy

Abstract: A pilarnil, ilk olarak Nicola Iliesu tarafından 1980 yılında Romanya'daki psikotik, nörodejeneratif ve cinsel rahatsızlıklara sahip olan yaşlılarda kullanılan erkek bal arısı (Apis mellifera) homojenatıdır. Yüksek besin değerine sahip olup ucuz bir biyolojik aktif madde kaynağıdır. İçeriğinde su (%65-75), proteinler (%9-12), karbohidratlar (%6-12), yağ asitleri ve lipitler (%3,5-8) K, Na, Ca, Mg mineralleri (%1-1,5), amino asitler (treonin, lösin, izolösin, metiyonin) ve ayrıca testosteron, prolaktin, progeste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…performance. [13,36] In this study, BDL administration increased testosterone, growth hormone production and stimulated testes growth in Saanen GMK observed after 135 days at the end of the monitoring period. Similarly, Shoinbayeva et al (2017) reported that the rams' genotypes had lower plasma testosterone concentrations than our findings.…”
Section: Androgenic Effect Of Bdlmentioning
confidence: 49%
“…performance. [13,36] In this study, BDL administration increased testosterone, growth hormone production and stimulated testes growth in Saanen GMK observed after 135 days at the end of the monitoring period. Similarly, Shoinbayeva et al (2017) reported that the rams' genotypes had lower plasma testosterone concentrations than our findings.…”
Section: Androgenic Effect Of Bdlmentioning
confidence: 49%
“…If the mixture is dried until 4% humidity, product is stable at 4 to 8 • C for 2-3 years [32,68]. Due to the different production technologies (extraction, lyophilization, thermal drying, adsorption, stabilization, mixing), the preparations based on the drone brood have a non-permanent qualitative and quantitative composition, have different severity of nutritional and therapeutic properties, characterized by a different shelf life [16].…”
Section: Drone Brood As Dietary Supplementmentioning
confidence: 99%
“…It was discovered by the Romanian apitherapist Nicolae V. Iliesiu. Etymologically, the term originates from "api" for bee, "lar" for larvae, and "nil" as a shortened form of its discoverer's name, Nicholae Iliesiu [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is physically and chemically similar to royal jelly and has a homogeneous milky consistency. Apilarnil has an average of 25–35 % dry matter, 9–12 % protein, 6–10 % carbohydrate, 5–8 % lipid, 2 % ash, and 3 % unidentified substances and androgenic hormones [1–3] . In the chemical analysis of honey bee male larvae, it was determined that the raw samples include 73.6 % water, 10 % protein, 3.5 % lipid, 12.2 % carbohydrate, 0.7 % ash and their energy value was 120.3 Kcal/100 g. In the same study, lyophilized samples contained 3 % water, 32 % protein, 24.2 % lipid, 38.9 % carbohydrates, and 2.7 % ash, and the energy value was reported as 501.4 Kcal/100 g [4,5] .…”
Section: Introductionmentioning
confidence: 99%